Loving the World We Are: Anthropology and Relationality in Laudato si' - Kohlhaas, Jacob M. (Journal of religious ethics, 2019)
There is a tension between Laudato si's consistent emphasis on relationships and interconnectedness and its acceptance of anthropocentrism. While Laudato si' does reject certain problematic forms of anthropocentrism, the encyclical does not assert an alternative to this traditional framework. This article contends that "relatiocentrism" provides the best avenue for developing the convictions expressed within Laudato si' while moving beyond the limitations of the encyclical itself. In so doing, this essay explores the use of narrative as a means of shaping identity by mapping significant relationships and points of meaning. It examines the central anthropological claims of the encyclical and the tensions these create with anthropocentric narratives. And it examines relatiocentrism in light of the biblical creation accounts, the eschatological perspective of Laudato si', and virtue ethics. The essay concludes by suggesting further theological and moral implications of this shift in perspective.